# Nesbitt's inequality

In mathematics, Nesbitt's inequality is a special case of the Shapiro inequality. It states that for positive real numbers a, b and c we have:

${\frac {a}{b+c}}+{\frac {b}{a+c}}+{\frac {c}{a+b}}\geq {\frac {3}{2}}.$ ## Proof

### First proof: AM-HM inequality

By the AM-HM inequality on $(a+b),(b+c),(c+a)$ ,

${\frac {(a+b)+(a+c)+(b+c)}{3}}\geq {\frac {3}{\frac {1}{a+b}}+{\frac {1}{a+c}}+{\frac {1}{b+c}}}}.$ Clearing denominators yields

$((a+b)+(a+c)+(b+c))\left({\frac {1}{a+b}}+{\frac {1}{a+c}}+{\frac {1}{b+c}}\right)\geq 9,$ from which we obtain

$2{\frac {a+b+c}{b+c}}+2{\frac {a+b+c}{a+c}}+2{\frac {a+b+c}{a+b}}\geq 9$ by expanding the product and collecting like denominators. This then simplifies directly to the final result.

### Second proof: Rearrangement

Suppose $a\geq b\geq c$ , we have that

${\frac {1}{b+c}}\geq {\frac {1}{a+c}}\geq {\frac {1}{a+b}}$ define

${\vec {x}}=(a,b,c)$ ${\vec {y}}=\left({\frac {1}{b+c}},{\frac {1}{a+c}},{\frac {1}{a+b}}\right)$ The scalar product of the two sequences is maximum because of the rearrangement inequality if they are arranged the same way, call ${\vec {y}}_{1}$ and ${\vec {y}}_{2}$ the vector ${\vec {y}}$ shifted by one and by two, we have:

${\vec {x}}\cdot {\vec {y}}\geq {\vec {x}}\cdot {\vec {y}}_{1}$ ${\vec {x}}\cdot {\vec {y}}\geq {\vec {x}}\cdot {\vec {y}}_{2}$ ### Third proof: Hilbert's Seventeenth Problem

The following identity is true for all $a,b,c:$ ${\frac {a}{b+c}}+{\frac {b}{a+c}}+{\frac {c}{a+b}}={\frac {3}{2}}+{\frac {1}{2}}\left({\frac {(a-b)^{2}}{(a+c)(b+c)}}+{\frac {(a-c)^{2}}{(a+b)(b+c)}}+{\frac {(b-c)^{2}}{(a+b)(a+c)}}\right)$ This clearly proves that the left side is no less than ${\frac {3}{2}}$ for positive a, b and c.

Note: every rational inequality can be solved by transforming it to the appropriate identity, see Hilbert's seventeenth problem.

### Fourth proof: Cauchy–Schwarz

Invoking the Cauchy–Schwarz inequality on the vectors $\displaystyle \left\langle {\sqrt {a+b}},{\sqrt {b+c}},{\sqrt {c+a}}\right\rangle ,\left\langle {\frac {1}{\sqrt {a+b}}},{\frac {1}{\sqrt {b+c}}},{\frac {1}{\sqrt {c+a}}}\right\rangle$ yields

$((b+c)+(a+c)+(a+b))\left({\frac {1}{b+c}}+{\frac {1}{a+c}}+{\frac {1}{a+b}}\right)\geq 9,$ which can be transformed into the final result as we did in the AM-HM proof.

### Fifth proof: AM-GM

We first employ a Ravi substitution: let $x=a+b,y=b+c,z=c+a$ . We then apply the AM-GM inequality to the set of six values $\left\{x^{2}z,z^{2}x,y^{2}z,z^{2}y,x^{2}y,y^{2}x\right\}$ to obtain

${\frac {\left(x^{2}z+z^{2}x\right)+\left(y^{2}z+z^{2}y\right)+\left(x^{2}y+y^{2}x\right)}{6}}\geq {\sqrt[{6}]{x^{2}z\cdot z^{2}x\cdot y^{2}z\cdot z^{2}y\cdot x^{2}y\cdot y^{2}x}}=xyz.$ Dividing by $xyz/6$ yields

${\frac {x+z}{y}}+{\frac {y+z}{x}}+{\frac {x+y}{z}}\geq 6.$ Substituting out the $x,y,z$ in favor of $a,b,c$ yields

${\frac {2a+b+c}{b+c}}+{\frac {a+b+2c}{a+b}}+{\frac {a+2b+c}{c+a}}\geq 6$ ${\frac {2a}{b+c}}+{\frac {2c}{a+b}}+{\frac {2b}{a+c}}+3\geq 6$ which then simplifies to the final result.

### Sixth proof: Titu's Screw lemma

Titu's lemma, a direct consequence of the Cauchy–Schwarz inequality, states that for any sequence of $n$ real numbers $(x_{k})$ and any sequence of $n$ positive numbers $(a_{k})$ , $\displaystyle \sum _{k=1}^{n}{\frac {x_{k}^{2}}{a_{k}}}\geq {\frac {(\sum _{k=1}^{n}x_{k})^{2}}{\sum _{k=1}^{n}a_{k}}}$ . We use its three-term instance with $x$ -sequence $a,b,c$ and $a$ -sequence $a(b+c),b(c+a),c(a+b)$ :

${\frac {a^{2}}{a(b+c)}}+{\frac {b^{2}}{b(c+a)}}+{\frac {c^{2}}{c(a+b)}}\geq {\frac {(a+b+c)^{2}}{a(b+c)+b(c+a)+c(a+b)}}$ By multiplying out all the products on the lesser side and collecting like terms, we obtain

${\frac {a^{2}}{a(b+c)}}+{\frac {b^{2}}{b(c+a)}}+{\frac {c^{2}}{c(a+b)}}\geq {\frac {a^{2}+b^{2}+c^{2}+2(ab+bc+ca)}{2(ab+bc+ca)}},$ which simplifies to

${\frac {a}{b+c}}+{\frac {b}{c+a}}+{\frac {c}{a+b}}\geq {\frac {a^{2}+b^{2}+c^{2}}{2(ab+bc+ca)}}+1.$ By the rearrangement inequality, we have $a^{2}+b^{2}+c^{2}\geq ab+bc+ca$ , so the fraction on the lesser side must be at least $\displaystyle {\frac {1}{2}}$ . Thus,

${\frac {a}{b+c}}+{\frac {b}{c+a}}+{\frac {c}{a+b}}\geq {\frac {3}{2}}.$ ### Seventh proof: Homogeneous

As the left side of the inequality is homogeneous, we may assume $a+b+c=1$ . Now define $x=a+b$ , $y=b+c$ , and $z=c+a$ . The desired inequality turns into ${\frac {1-x}{x}}+{\frac {1-y}{y}}+{\frac {1-z}{z}}\geq {\frac {3}{2}}$ , or, equivalently, ${\frac {1}{x}}+{\frac {1}{y}}+{\frac {1}{z}}\geq 9/2$ . This is clearly true by Titu's Lemma.

### Eighth proof: Jensen inequality

Define $S=a+b+c$ and consider the function $f(x)={\frac {x}{S-x}}$ . This funcion can be shown to be convex in $[0,S]$ and, invoking Jensen inequality, we get

$\displaystyle {\frac {{\frac {a}{S-a}}+{\frac {b}{S-b}}+{\frac {c}{S-c}}}{3}}\geq {\frac {S/3}{S-S/3}}.$ A straightforward computation yields

${\frac {a}{b+c}}+{\frac {b}{c+a}}+{\frac {c}{a+b}}\geq {\frac {3}{2}}.$ 